2014
DOI: 10.1111/1469-0691.12407
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient costs, mortality and 30-day re-admission in patients with central-line-associated bloodstream infections

Abstract: Previous work has suggested that central-line-associated bloodstream infection (CLABSI) is associated with increased costs and risk of mortality; however, no studies have looked at both total and variable costs, and information on outcomes outside of the intensive-care unit (ICU) is sparse. The aim of this study was to determine the excess in-hospital mortality and costs attributable to CLABSI in ICU and non-ICU patients. We conducted a retrospective cohort and cost-of-illness study from the hospital perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 28 publications
2
105
1
2
Order By: Relevance
“…3 Published estimates of attributable costs of CLABSI in adult patients have varied over years and across hospital settings, 4,5 with 2010 estimates of $50 094 per event from 1 tertiary care, academic medical center. 6 A pediatric study found an attributable 2008 dollar cost of $33 039 per CLABSI in a sample of 22 critically ill children. 7 Quality improvement collaboratives, largely based in ICUs, have demonstrated that most CLABSIs are preventable.…”
mentioning
confidence: 99%
“…3 Published estimates of attributable costs of CLABSI in adult patients have varied over years and across hospital settings, 4,5 with 2010 estimates of $50 094 per event from 1 tertiary care, academic medical center. 6 A pediatric study found an attributable 2008 dollar cost of $33 039 per CLABSI in a sample of 22 critically ill children. 7 Quality improvement collaboratives, largely based in ICUs, have demonstrated that most CLABSIs are preventable.…”
mentioning
confidence: 99%
“…[27][28][29] More importantly, CLABSI prevention can reduce morbidity. 30 Following implementation and maintenance of the bundle in LTACHs, the CLABSI rate was reduced significantly (29%), from a SIR of 1.28 to a SIR less than 1.0 and no different from the expected CLABSI rate, because the mean 95% CI of the CLABSI SIR includes the expected value of 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…16 Additionally, our model included a baseline mortality rate for ICU (13.5%) [19][20][21] and general ward patients (2%) 22 and the relative risk of mortality for patients with CLABSI (2.27). 23 …”
Section: Input Parametersmentioning
confidence: 99%